Scaling up the Bioconversion of Cheese Whey Permeate into Fungal Oil by Mucor circinelloides. (2nd June 2020) - Chan, Lauryn G.; Dias, Fernanda F. G.; Saarni, Andrew; Cohen, Joshua; Block, David; Taha, Ameer Y.; de Moura Bell, Juliana M. L. N.
Abstract: The bioconversion of hydrolyzed whey permeate into an oil‐rich biomass by Mucor circinelloides was scaled up from 250 mL to 4 L with the use of an aerated stirred tank bioreactor. Biomass production and oil accumulation were strongly influenced by agitation speed (99–451 rpm) and aeration rate (0.29–1.70 vvm). Higher agitation and aeration rates (e.g., >400 rpm, >1 vvm), resulted in significantly higher biomass yield due to increased oxygen transfer capabilities and better mixing. Additionally, oil accumulation in the fungal biomass was related to high agitation (>400 rpm), while aeration (0.5–1.5 vvm) had no significant effect within the range evaluated. The predictive model was validated at the optimal conditions of 450 rpm and 1 vvm. Maximum biomass yield of 10.7 g L −1 and lipid content of 32% dry biomass were achieved during 120 hours of fermentation. Simultaneous optimization of agitation and aeration in a bioreactor was found to not only improve fungal growth but also lipid content (24% vs. 32%), lipid yield (2.2 vs. 3.1 g L −1 ) and γ‐linoleic production (73–464 mg L −1 ) compared to that of shake‐flask. This study resulted in a scaled‐up and optimized fermentation process that increased production of M. circinelloides biomass for subsequent use as raw material for food, feed, and fuel applications. This signifies a starting point for further studies aimed at assessing the development of a fully functioning fungi‐to‐food/fuel system on an industrial scale for several agricultural streams.